Beyond Performance Ratings: The Long Road to Effective Performance Management. Issue 2 (4th July 2016) - Cardy, Robert L.; Munjal, Deeksha
Abstract : Performance evaluation has long been a source of dissatisfaction for practitioners and a focus of research for scholars. The current call for the elimination of performance ratings is not new. This commentary considers the quality perspective as a historical context in which performance ratings were, at best, considered a misguided management tool. Although the current debate doesn't seem to be philosophically based, it may be useful to recognize that serious questions regarding performance ratings have come up before. Potential measurement problems with performance ratings are considered. It is concluded that performance ratings are not the major problem for performance management. Possible sources of problems with performance management are considered. Directions for improvement are discussed.